2010
DOI: 10.1002/ajh.21609
|View full text |Cite
|
Sign up to set email alerts
|

IgG‐λ plasma cell myeloma with cytoplasmic azurophilic inclusion bodies

Abstract: A 70-year-old man with a history of coronary artery disease status post coronary artery bypass graft presented to his urologist with 1 month urinary frequency. Prostate examination was unremarkable, but a routine urine analysis revealed glucosuria (31). Additional laboratory tests confirmed the diagnosis of type II diabetes mellitus. As a part of the initial investigation, routine laboratory tests revealed elevated total serum protein (9.4 g/dL; reference range, 6.4-8.2 g/dL). Complete blood count demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
5
1
Order By: Relevance
“…Additionally, there is no known cytogenetic association as most reports have not provided results of karyotyping. In one report, however, a complex hyperdiploid clone comprising multiple numerical and structural abnormalities was described 4. This is in contrast to our case where hypodiploid abnormalities were present.…”
contrasting
confidence: 99%
“…Additionally, there is no known cytogenetic association as most reports have not provided results of karyotyping. In one report, however, a complex hyperdiploid clone comprising multiple numerical and structural abnormalities was described 4. This is in contrast to our case where hypodiploid abnormalities were present.…”
contrasting
confidence: 99%
“…While myeloma with cytoplasmic inclusions has been reported previously (1,2), the present case is unique as the cytoplasm of the plasma cells was strikingly foamy on the histologic section mimicking a Niemann-Pick disease. The case emphasizes the diagnostic significance of correlating morphology with clinical findings, because it could have been initially considered to be an unidentified storage disease resulting in unnecessary diagnostic workup or even misdiagnosis if pertinent laboratory data were not available.…”
supporting
confidence: 48%
“…The significance of the presence of cytoplasmic granules in myeloma cells is poorly understood. The GM cells are considered to be detectable infrequently because the study about large number of cases with the GM cells has not been demonstrated, and only several cases with cytoplasmic granules in myeloma cells were reported . In our study, 20.5% of MM patients displayed cytoplasmic granules, and hence we speculated that GM cells could be detected occasionally.…”
Section: Discussionmentioning
confidence: 58%